Prediction of Unilateral Meniere's Disease Attack Using Inner Ear Test Battery. Issue 3 (May 2020) - Wu, Po-Hsuan; Chang, Chih-Ming; Lo, Wu-Chia; Wang, Chi-Te; Wen, Ming-Hsun; Huang, Tsung-Wei; Young, Yi-Ho; Cheng, Po-Wen
Abstract : Objectives: In the clinical setting, a variety of inner ear test results are obtained from patients with unilateral Meniere's disease (MD). In this study, the authors use inner ear test results as parameters to illustrate the relationship between inner ear function and vertigo attack frequency. Design: We retrospectively enrolled 50 unilateral MD patients. In addition to clinical symptoms, the results of pure-tone audiometry and caloric, acoustic cervical vestibular-evoked myogenic potential (cVEMP), galvanic cVEMP, vibratory ocular VEMP (oVEMP), and galvanic oVEMP tests were collected via chart review. The multiple linear regression method was used to examine which independent variables have a statistically significant influence on vertigo attacks. Results: In affected ears, the abnormal rate of the caloric, acoustic cVEMP, galvanic cVEMP, vibratory oVEMP, and galvanic oVEMP tests was 74%, 76%, 48%, 34%, and 30%, respectively. According to the regression model, the abnormal galvanic cVEMP response and abnormal galvanic oVEMP response had significantly negative correlations with the frequency of vertigo attacks after logarithmic transformation. A predictive model for disease attack frequency using significant parameters and their regression coefficients was proposed: Conclusions: Using the proposed model with galvanic VEMP, clinicians could develop better strategies to manage vertigo attacks in patients with MD.